2021
DOI: 10.1038/s41598-021-90357-6
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated equine estrogen used in postmenopausal women associated with a higher risk of stroke than estradiol

Abstract: This study aimed to evaluate the risk of ischemic stroke (IS) in hormone therapy (HT) with oral conjugated equine estrogen (CEE) and estradiol (E2) in postmenopausal women in Taiwan. A retrospective cohort study was conducted using the Taiwan National Health Insurance Research Database, a population-based healthcare claims dataset. Eligible women, aged 40–65 years, who received HT with E2 and CEE orally were enrolled. The primary outcome was IS. Propensity score matching with menopausal age and comorbidities w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In a retrospective cohort study in the Taiwan National Health Insurance Research Database, among females 40 to 65 years of age treated with postmenopausal hormone therapy, the incidence of ischemic stroke was 1.17-fold higher in females treated with conjugated equine estrogen than in those treated with estradiol (4.24 per 1000 person-years versus 3.61 per 1000 person-years; aHR, 1.23 [95% CI 1.05–1.44]). 146…”
Section: Stroke (Cerebrovascular Diseases)mentioning
confidence: 99%
“…In a retrospective cohort study in the Taiwan National Health Insurance Research Database, among females 40 to 65 years of age treated with postmenopausal hormone therapy, the incidence of ischemic stroke was 1.17-fold higher in females treated with conjugated equine estrogen than in those treated with estradiol (4.24 per 1000 person-years versus 3.61 per 1000 person-years; aHR, 1.23 [95% CI 1.05–1.44]). 146…”
Section: Stroke (Cerebrovascular Diseases)mentioning
confidence: 99%
“…In a retrospective cohort study in the Taiwan National Health Insurance Research Database, among females 40 to 65 years of age treated with postmenopausal hormone therapy, the incidence of ischemic stroke was 1.17-fold higher in females treated with conjugated equine estrogen than in those treated with estradiol (4.24 per 1000 person-years versus 3.61 per 1000 person-years; aHR, 1.23 [95% CI, 1.05–1.44]). 125…”
Section: Stroke (Cerebrovascular Diseases)mentioning
confidence: 99%
“…Furthermore, epidemiological analysis of AD patients has shown that E2 use was of greater benefit to verbal memory than CEE [ 74 , 75 ]. Chang et al [ 194 ] demonstrated similar findings, showing that the action of CEEs caused a 1.17-fold increase in the incidence of ischemic stroke compared to users of E2. These results are likely dictated by differences in each formulation’s opportunity for conversion and binding affinity.…”
Section: Additional Factorsmentioning
confidence: 69%